Shakespeare and the Legacy of Loss - Anderson, Emily Hodgson, 1977- (Book collections on Project MUSE., 2018)
"This book looks at a British actor from the 1700s, David Garrick. By playing Shakespeare, Garrick raised the playwright to a position of new national importance, but in the process of doing so, he also activated Shakespeare as the social and cultural center around which he, and many other actors and even novelists, could work out questions about how to resist the evanescence of theater and life. How could the artist who stakes his fame on an ephemeral form of art be celebrated or preserved? How do approaches to commemoration change in light of these attempts? And how did Shakespeare become an emblem to other artists for how such preservation could be achieved? These are questions that Garrick, through Shakespeare, was able to ask, and questions that, thanks to Garrick, others would then take up. The chapters that follow tell the story of the answers they obtained"--